1996
DOI: 10.1152/jappl.1996.81.4.1677
|View full text |Cite
|
Sign up to set email alerts
|

Greater initial adaptations to submaximal muscle lengthening than maximal shortening

Abstract: Hortobágyi, Tibor, Jason Barrier, David Beard, John Braspennincx, Peter Koens, Paul Devita, Line Dempsey, and Jean Lambert.Greater initial adaptations to submaximal muscle lengthening than maximal shortening. J. Appl. Physiol.81(4): 1677–1682, 1996.—The purpose of this study was to compare the short-term strength and neural adaptations to eccentric and concentric training at equal force levels. Forty-two sedentary women (age = 21.5 yr) were ranked based on the initial quadriceps strength score, and trios of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
128
3
11

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(159 citation statements)
references
References 21 publications
17
128
3
11
Order By: Relevance
“…Because ECC contractions exert a much greater muscle force than CON contractions, ERT has the capability of 'overloading' the muscle to a greater extent, which can result in greater increases in strength and size. [17][18][19] In this study, an increase in 1RM was observed both in the ERT and CRT groups, but the degree of increase was greater in the ERT than in the CRT group. These results suggest that ERT, which had a quick lifting and Pulse wave velocity, which is an index of arterial stiffness, 20,21 is known to be a strong independent predictor of cardiovascular morbidity in patients with hypertension and type II diabetes, and of all-cause mortality in patients with hypertension and end-stage renal disease.…”
Section: Discussionmentioning
confidence: 42%
“…Because ECC contractions exert a much greater muscle force than CON contractions, ERT has the capability of 'overloading' the muscle to a greater extent, which can result in greater increases in strength and size. [17][18][19] In this study, an increase in 1RM was observed both in the ERT and CRT groups, but the degree of increase was greater in the ERT than in the CRT group. These results suggest that ERT, which had a quick lifting and Pulse wave velocity, which is an index of arterial stiffness, 20,21 is known to be a strong independent predictor of cardiovascular morbidity in patients with hypertension and type II diabetes, and of all-cause mortality in patients with hypertension and end-stage renal disease.…”
Section: Discussionmentioning
confidence: 42%
“…Hortobagyi et al 26 examined the dependency of muscle increase on contraction modes and reported that CON muscle strength was significantly increased by CRT, whereas ECC muscle strength was significantly increased by ERT. Since the measured 1RM in this study was CON, it was considered that the increase in muscle strength was dependent on the contraction mode.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from studies during the last decade suggest that high-intensity resistance training incorporating eccentric contractions can offer some advantages over more traditional training strategies to increase muscle strength and mass in older adults (Hortobagyi and De Vita., 2000;LaStayo et al, 2003a;Onambele et al, 2008;Reeves et al, 2009). The high metabolic efficiency (LaStayo et al, 2000) and faster adaptations observed with eccentric training (Hortobagyi et al, 1996) make it especially appealing in clinical situations after periods of immobilization or in the most debilitated old individuals (Hortobagyi and De Vita, 2000).…”
Section: Implications For Training and Rehabilitation Of The Elderlymentioning
confidence: 99%